2022
DOI: 10.5051/jpis.2104040202
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement in conjunction with guided bone regeneration and/or connective tissue grafts: an experimental study in canines

Abstract: Purpose: This study was conducted to assess the effect of hard and/or soft tissue grafting on immediate implants in a preclinical model. Methods: In 5 mongrel dogs, the distal roots of P2 and P3 were extracted from the maxilla (4 sites in each animal), and immediate implant placement was performed. Each site was randomly assigned to 1 of the following 4 groups: i) gap filling with guided bone regeneration (the GBR group), ii) subepithelial connective tissue grafting (the SCTG group), iii) GBR and SCTG (the GBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These values are smaller than those found in the present study (between 3.51 and 3.66 mm for total tissue thickness, and between 1.63 and 2.55 mm for soft‐tissue thickness). The main difference between these two studies is in the presence of the buccal bone plate: in the previous study, the tissue at the measured levels was predominantly soft tissue because of loss of the buccal plate (Lim et al, 2022). This indicates that the effect of soft‐tissue augmentation might be affected by the presence and thickness of the underlying hard tissue to some extent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These values are smaller than those found in the present study (between 3.51 and 3.66 mm for total tissue thickness, and between 1.63 and 2.55 mm for soft‐tissue thickness). The main difference between these two studies is in the presence of the buccal bone plate: in the previous study, the tissue at the measured levels was predominantly soft tissue because of loss of the buccal plate (Lim et al, 2022). This indicates that the effect of soft‐tissue augmentation might be affected by the presence and thickness of the underlying hard tissue to some extent.…”
Section: Discussionmentioning
confidence: 96%
“…A previous preclinical canine study evaluated the IP protocol using several regenerative approaches (GBR, CTG and their combination) and found that the median tissue thickness ranged between 0.78 and 1.57 mm (at the IS, IS−1 and IS+1 levels) in the group with CTG (Lim et al, 2022). These values are smaller than those found in the present study (between 3.51 and 3.66 mm for total tissue thickness, and between 1.63 and 2.55 mm for soft‐tissue thickness).…”
Section: Discussionmentioning
confidence: 99%
“…Bone regeneration replacement materials must be biocompatible, biodegradable, easy to apply, effective for bone repair, and highly adaptable to bone defects ( Helal et al, 2016 , Veljanovski et al, 2021 , Wang et al, 2002 ). Various scaffold types and natural or synthetic materials, such as metals, ceramics, and polymers, have been used to stimulate and enhance bone regeneration ( Kim et al, 2021 , Lim et al, 2021 ). Each option has different osteoinductive, osteoconductive, biocompatibility, biodegradability, and chemical properties, necessitating various techniques for their design and application ( Zimmerling et al, 2021 , Eldeeb et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%